Cervical Lymph Node Metastasis in High-Grade Transformation of Head and Neck Adenoid Cystic Carcinoma: A Collective International Review. Issue 3 (March 2016) - Hellquist, Henrik; Skálová, Alena; Barnes, Leon; Cardesa, Antonio; Thompson, Lester; Triantafyllou, Asterios; Williams, Michelle; Devaney, Kenneth; Gnepp, Douglas; Bishop, Justin; Wenig, Bruce; Suárez, Carlos; et al.
Abstract Adenoid cystic carcinoma (AdCC) is among the most common malignant tumors of the salivary glands. It is characterized by a prolonged clinical course, with frequent local recurrences, late onset of metastases and fatal outcome. High-grade transformation (HGT) is an uncommon phenomenon among salivary carcinomas and is associated with increased tumor aggressiveness. In AdCC with high-grade transformation (AdCC–HGT), the clinical course deviates from the natural history of AdCC. It tends to be accelerated, with a high propensity for lymph node metastasis. In order to shed light on this rare event and, in particular, on treatment implications, we undertook this review: searching for all published cases of AdCC-HGT. We conclude that it is mandatory to perform elective neck dissection in patients with AdCC-HGT, due to the high risk of lymph node metastases associated with transformation.